Tumor-associated macrophages respond to chemotherapy by detrimental transcriptional reprogramming and suppressing stabilin-1 mediated clearance of EGF - Larionova, Irina; Kiselev, Artem; Kazakova, Elena; Liu, Tengfei; Patysheva, Marina; Iamshchikov, Pavel; Liu, Quan; Mossel, Dieuwertje M.; Riabov, Vladimir; Rakina, Militsa; Sergushichev, Alexey; Bezgodova, Natalia; et al. (Frontiers in Immunology, 2023)
Tumor resistance to chemotherapy and metastatic relapse account for more than 90% of cancer specific mortality. Tumor-associated macrophages (TAMs) can process chemotherapeutic agents and impair their action. Little is known about the direct effects of chemotherapy on TAMs. Here we show that chemotherapeutic agent cisplatin can initiate detrimental transcriptional and functional programs in TAMs, without significant impairment of their viability. We focused on the clearance function of TAMs that controls composition of tumor microenvironment. For the first time we demonstrated, that TAMs’ scavenger receptor stabilin-1 is responsible for the clearance of EGF, a potent stimulator of tumor growth. Cisplatin suppressed both overall and EGF-specific endocytosis in TAMs by bidirectional mode: suppression of positive regulators and stimulation of negative regulators of endocytosis, with strongest effect on SYT11, confirmed in patients with breast cancer. Our data demonstrate that synergistic action of cytostatic agents and innovative immunomodulators is required to overcome cancer therapy resistance.